Assessing the Efficiency of Waqf Institutions in Indonesia: A Non-Parametric Approach - Maulida, Syahdatul; Mi'raj, Denizar Abdurrahman (Islamic Social Finance, 2023)
Maintaining waqf performance is important to ensure that waqf assets are well managed. The effectiveness and efficiency of waqf asset management is crucial so that progress can be measured. This study aims to evaluate the efficiency of waqf institutions in Indonesia during the 2015-2021 period using the non-parametric Data Envelopment Analysis (DEA) approach. The research object includes six waqf institutions in Indonesia, with data obtained from the annual reports of each institution. The results show that during the observation period, no waqf institution has managed to achieve the optimum efficiency score. In addition, the efficiency trend of waqf institutions shows a downward trend, especially during the Covid-19 pandemic. Through potential improvement analysis, this study succeeded in identifying the main factors causing the inefficiency of waqf institutions. In particular, output variables such as waqf fund receipts and disbursements become the main focal points for efficiency improvement.